THE USE A COMBINATION OF ENDOBRONCHIAL ULTRASOUND-GUIDED FINE-NEEDLE ASPIRATION AND TRANSESOPHAGEAL ENDOSCOPIC ULTRASOUND-GUIDED FINE-NEEDLE ASPIRATION AS A TOOLS TO MAKE A DIAGNOSIS AND STAGING OF LUNG CANCER - Arika Fermiawan, I Gusti Ngurah; Made Artika, I Dewa (E-Jurnal Medika Udayana; vol 2 no1 (2013):e-jurnal medika udayana)
Endobronchial Ultrasound-Guided Fine-Needle Aspiration (EBUS-FNA) and Transesophageal Endoscopic Ultrasound-Guided Fine-Needle Aspiration (EUS-FNA) is a minimally invasive technique, safe and cost effective, which uses ultrasound assistance in determining the diagnosis and staging of lung cancer. EBUS using bronchoscopy whereas EUS using endoscopy, where both of those tools  integrated by ultrasound and needle aspiration. EBUS method can only check for mediastinal Lymphoma in lymph nodes anterior whereas EUS can only check the lymph nodes on the posterior region. The use of a combination of EUS and EBUS will increase the area of examination for mediastinal Lymphoma lymph nodes as well as the sensitivity and specificity in defining the diagnosis of lung cancer. Lymph node positions itself according to the according to the American Joint Committee on Cancer and the Union Internationale Contre le Cancer. Overall, these methods do not cause fatal complications if compared to other invasive diagnostic procedures.
Keywords: bronchocopy, endoscopy, ultrasound, lung cancer